Analisis Perspektif Eclipse of Reason Max Horkheimer terhadap Fenomena Echo Chamber - Fajar Nur Bahri; Astri Amanda Putri; Fathir Al Fath Harahap (Jurnal Budi Pekerti Agama Islam, 2026)
Social media, initially projected as a democratic discourse space, has instead become trapped in the echo chamber phenomenon, narrowing the intellectual horizons of its users. This research aims to analyze the echo chamber phenomenon on social media through the lens of Max Horkheimer’s critical theory, specifically the concept of the "Eclipse of Reason." The method used in this study is qualitative descriptive with a literature study and philosophical analysis approach. The results indicate that social media algorithms have shifted objective reason into instrumental reason, where truth is measured solely by efficacy and confirmation of personal beliefs. The analysis in this article concludes that social media functions as an "eclipse of reason" machine that stifles the critical reasoning abilities of individuals. This process occurs when reason is no longer used to critically dissect reality but serves merely as a technical tool to adapt to homogeneous information flows. The death of critical reason is not merely a technical byproduct of algorithms but a manifestation of the dominance of formal rationality that sidelines human values in the digital sphere.